Synthesis, Characterization, and Investigation of Performance of Fe-MOF and Fe-MOF/Fe3O4 in Adsorption and Release of Naproxen as a Non-steroid Anti-inflammatory Drug (NSAID): Synthesis, Characterization, and Investigation of Performance of Fe-MOF - Hosseini, Sayyde Shadi; Hosseini, Seyed Ali; Broukanlou, Mahin (Iranian Journal of Pharmaceutical Sciences, 2025)
Developing materials with a high capacity for drug adsorption and slow-releasing properties is promising in drug delivery. Metal-organic frameworks (MOFs) are materials with high adsorption and desorption capacities. Therefore, they can be very effective in targeted drug therapy. In this study, two Fe-MIL101 samples with different synthesis times (24 and 48 hours) were synthesized by solvothermal method and used as a naproxen carrier for the first time. The samples were analyzed using BET, FT-IR, XRD, and FESEM structural analyses at the nanoscale. The pHpzc of the Fe-MIL101 (48h) and Fe-MIL101/Fe3O4 was determined to be 3.3 and 3.5, respectively. The adsorption of the Naproxen on Fe-MIL-101/Fe3O4 followed the Freundlich adsorption isotherm (R²=0.996), indicating the multilayer adsorption of Naproxen molecules on the carriers. The release of naproxen from carriers was investigated at a phosphate-buffered saline (PBS( with a pH of 7.4 (the pH of human blood). The variables of release time, carrier synthesis time, and pH of the environment were considered in this study. The most effective release was with Fe-MIL-101/Fe3O4 synthesized over 48 hours. This method followed the kinetic model of Korsmeyer-Peppas (R²= 0.9843) with a release exponent (n) of 0.63, meaning that the naproxen release from MOFs follows the non-Fickian mechanism. To develop a magnetic and slow-releasing carrier, Fe-MIL-101/Fe3O4 was synthesized. The studies showed that naproxen release from Fe-MIL-101/Fe3O4 is slow and takes a long time. The n in Korsmeyer-Peppas mole for naproxen release from Fe-MIL-101/Fe3O4 was 0.886, indicating a case II transport mechanism for naproxen release with a constant release rate. The findings highlight the significant potential of Fe-MIL-101/Fe3O4 for enhancing targeted drug delivery, underscoring its importance in improving therapeutic outcomes.